Contact sensitization in prurigo patients - Weisshaar, Elke (Contact dermatitis, 2016)
There are no studies on contact allergy in patients with prurigo. With itch being important in the pathophysiology of prurigo diseases and being a symptom of allergic contact dermatitis, we aimed to investigate contact allergy in patients suffering from prurigo. Objectives Exploratory analysis of patch test results in prurigo patients. Materials and methods a retrospective analysis of data of the Information Network of Departments of Dermatology, 2005-2014, was performed. Results Of 116 744 patch tested patients, 639 (0.55%) were diagnosed with prurigo. The median age was 61 years, 286 (45%) were pensioners, and 252 (39.5%) had generalized prurigo. The indication for patch testing was exclusion of contact allergy in 412 patients (64.5%), and 223 patients (35%) had at least one positive patch test reaction. There was no distinctive pattern of sensitization. Prurigo patients had significantly more (and stronger) reactions to the irritant control patch test with sodium lauryl sulfate than a control group (27.6% versus 21.0%). Conclusions Although prurigo is not a typical clinical manifestation of contact sensitization, our results indicate that patch testing in these patients may be helpful.